If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = x + y Solving 25 = x + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 25 + -1x = x + -1x + y Combine like terms: x + -1x = 0 25 + -1x = 0 + y 25 + -1x = y Add '-25' to each side of the equation. 25 + -25 + -1x = -25 + y Combine like terms: 25 + -25 = 0 0 + -1x = -25 + y -1x = -25 + y Divide each side by '-1'. x = 25 + -1y Simplifying x = 25 + -1y
| 6x-0.8x^2=0 | | 6.1(3.1+2.5)=15.3x-3.9 | | 3(31-12c)=82 | | 2(y-5)=24 | | 29y-50=24 | | 0=4-(4*1*c) | | 18-x=13 | | e+e+e+e+e=45 | | y=sin(x)cos(sin(x)) | | -37=P-18 | | -4X-5(8-4X)=15+5X | | x^2-2x+c=0 | | 6-x=11-3x | | 7(-2-3X)=91 | | y=5x^4 | | 3-6y=8 | | 3g+4=19 | | 3g+4= | | 5-4x=3+x | | 3x^2=10-2x | | 3x+4+3x-2=42 | | -7(1-4v)-8v=-167 | | 3y+5+2y+1=31 | | -3-5(3-6r)=-258 | | 2=8+4a | | -129=4(1-4b)-5 | | 5x+6=4x-4 | | 8(-2+4n)+4n=-196 | | 5x-3+2x=x+3 | | 10w^7+34w^6+12w^5= | | 3(x+1.31)=2x | | 2a(a-4)=0 |